STRATEGI KEPALA SEKOLAH DALAM MENGEMBANGKAN PROGRAM TAHFIZHUL QUR’AN SMP MUHAMMADIYAH 57 MEDAN - Rido, Muhammad; Harfiani, Rizka (Berajah Journal, 2025)
This study discusses the principal's strategy in developing the Tahfizhul Qur'an program at SMP Muhammadiyah 57 Medan. This type of investigation uses a qualitative method with a narrative type. Data collection techniques are through interview programs, observations and documents. The findings of this research are (1) planning strategy, namely conducting environmental analysis and formulating the vision-mission and objectives of the Tahfizhul Qur'an program. (2) Implementation strategy, namely: finding basic student problems in memorizing, grouping student memorization abilities, recruiting ideal Tahfizhul Qur'an teachers and running programs that are relevant to the Tahfizhul Qur'an program. (3) Implementation of evaluation, namely: conducting munaqasah exams and evaluating the performance of Tahfizhul Qur'an teachers. (4) Supporting and inhibiting factors for the tahfzihul Qur'an program, namely: supporters, namely capable classes, ideal teachers, suitability of learning methods and forms of evaluation that are carried out well. Inhibitors are lack of motivation, difficulty in memorizing and challenges in using android and (5) Efforts to reduce factors inhibiting the Tahfizhul Qur'an program at SMP Muhammadiyah 57 Medan, namely: providing routine motivation, conducting Al-Qur'an memorization training and providing rewards.